The Influence Of Work Stress And Work Environment On Employee Performance At Bareskrim Polres Kutai Timur Mediated By Work Motivation - Anggie Sulistiani Putri; Andriyastuti Suratman (Cita konsultindo, 2025)
This research investigates the impact of work stress and work environment on employee performance at Bareskrim Polres Kutai Timur, with work motivation as a mediating variable. A total of 95 respondents were selected using the Slovin formula to ensure representativeness. Data was collected through questionnaires and analyzed using SmartPLS 4.0 software.The findings reveal that work stress positively influences employee performance, suggesting that moderate levels of stress may enhance productivity. Conversely, the work environment negatively affects performance, implying that an unfavorable work atmosphere reduces productivity. Additionally, work motivation does not significantly impact performance nor mediate the relationship between work stress and employee performance.Moreover, the study highlights that the work environment has a greater influence on employee performance compared to work stress and motivation. The interaction between work stress and motivation indicates that these factors collectively shape performance outcomes. A supportive work environment is crucial in optimizing employee effectiveness.